NFB-18. Integration of single-nuclei RNA-sequencing and spatial transcriptomics to define the complex tumor microenvironment of NF1-associated plexiform neurofibroma and highly-aggressive malignant peripheral nerve sheath tumors. (3rd June 2022) - Amani, Vladimir; Donson, Andrew; Riemondy, Kent; Fu, Rui; Willard, Nicholas; Gilani, Ahmed; Norris, Gregory; Griesinger, Andrea; Harris, Faith; Grimaldo, Enrique; Foreman, Nicholas
Abstract: During formation of plexiform neurofibroma (PN), a complex tumor microenvironment (TME) develops, with recruitment of other cell types being critical for growth and progression. Approximately 10% of PN can undergo transformation into malignant peripheral nerve sheath tumors (MPNST) which is a substantial cause of mortality in older teenagers and young adults. We sought to apply single cell transcriptomic analysis to PN and MPNST to provide a clearer understanding of the complex TME and how this contributes to transformation and disease progression. Due to the cohesive cellularity of PN, single-cell RNA-sequencing is difficult and may result in a loss of detection of critical cellular subpopulations. Single-nuclei RNA-sequencing (snRNA-seq) is an alternative approach that can be applied to fibrous and bulk frozen tissues, such as NF1-associated PN. Our initial snRNA-seq analysis of PN indicates that PN have a TME comprised of a variety of cellular subpopulations, with the predominant fraction being fibroblast-like cells. snRNA-seq analysis of MPNST also shows high cellular heterogeneity, including distinct fibroblast-like subpopulations distinct from PN fibroblast clusters, increased proliferating populations and antigen presenting cells. MPNST cluster separately from PN, suggesting an evolutionary shift in tumor biology. We are currently validating our findings using Visium spatial transcriptomic profiling, allowing us to apply TME architectural context to the PN and MPNST subpopulations identified by snRNA-seq. These techniques provide a deeper understanding of the complex cellular heterogeneity of human PN and MPNST that has not previously been used to describe the TME of these tumors. The mechanisms of tumorigenesis and malignancy described can provide targets for novel therapies ultimately benefitting patients with these devastating tumors of childhood and early adulthood.